ASSESSMENT OF TOBACCO SCREENING AND SMOKING CESSATION RECOMMENDATION AMONG UROLOGISTS IN INDONESIA : A CROSS SECTIONAL ANALYSIS USING NATIONAL SURVEY - Pramana, Henry; Pramod, Sawkar Vijay; Safriadi, Ferry (Indonesian Urological Association, 2024)
Objective: This study aims to assess the urologist role on tobacco screening and smoking cessation among bladder cancer patients in Indonesia. Material & Methods: A questionnaire regarding tobacco uses screening and smoking cessation recommendation practice patterns was sent to urologists in Indonesia via Ikatan Ahli Urologi Indonesia (IAUI) or Indonesian Urological Association (IUA). The survey was established by Google Form and was sent by email. Responses were automatically integrated to Google spreadsheet. Results: Total of 111 responses from 569 urologists in Indonesia were received, and of the respondents 96% were male and 4% were female. 70% urologists always educate their patients about smoking as one of risk factor for bladder cancer and only 4% never did it. Most common answer for the reason is patients never ask their urologists about it (7%). More than half (59%) of urologists sometimes discuss smoking cessation and 78% always recommend quitting smoking. The majority of responders have never smoked cigarettes (56%), 35% were former smokers, and 9% were current smokers. Conclusion: This study revealed that majority of urologists always educate that smoking is one of risk factor for bladder cancer and recommend to quit smoking. However, only 37% always discuss tobacco use cessation with their patients. Keywords: Tobacco use, smoking cessation, bladder cancer, urologist.